Eu-mulheres: uma rede de suporte feminino como pulso para o experenciar em performance arte - Rodrigues, Marcella Nunes (2024)
This study is based on carrying out research on visual poetics, based on the process of creating a Performance Art that is articulated to gender issues, to care for oneself and for the other. affectivity and support among women, with a focus on the care of the female self-linked to the collective, this, linked to theoretical perspectives, both historical, social, and cultural, especially referring to the field of research with its performative materiality. It aligns with the publications of Taylor, Goldeberg and Melim, regarding Contemporary Art, especially regarding Performance Art. In this sense, the present work begins with the methodology of field research and autoethnography, to bring the proponent closer to women. Family women, women friends, women students who meet weekly through a dance network sharing experiences in movements. This approach seeks to provide the fabric of a female network that from the movement, reaches a gap in space and time for support, support, and care in the collective. In this proposal, relationships are present, affecting and being affected by the contact between the women involved and their diversities inserted in the research, resulting in the creation of a Performance Art that talks to the entire process resulting from the experiences during the research. The methodological procedure of an autoethnographic nature, is linked to the perspectives of Fortin, Versiani and Laplantine, being approached from the author's own point of view in relation to the ways of relationships and coexistence between women, demystifying the idea of competitiveness between them, on the contrary, promoting the support that can be established through the weaving of a network of women, sisterhood. Thus, it is expected, as partial results, which writing contributes to poetic and theoretical research in contemporary art, expanding knowledge about Performance Art, sorority, and the female network.